Glycemic Control and Serum and Urine Levels of Zinc and Magnesium in Diabetics in Calabar, Nigeria - Nsonwu, A.C.; Usoro, C.A.O.; Etukudo, M.H.; Usoro, I.N. (Pakistan Journal of Nutrition, 2005)
The effects of glycemic control on serum and urine concentrations of zinc and magnesium in diabetics in Calabar, Nigeria were determined. Serum and urine Zinc (Zn) and Magnesium (Mg), Fasting Plasma Glucose (FPG), Glycated Hemoglobin (HbA1c) and urine Creatinine (creat) levels were determined in sixty diabetic subjects and forty age matched non diabetic subjects in Calabar, Nigeria using colorimetric methods and atomic absorption spectrophotometry. The FPG, HbA1c, urine Zn and Mg levels were significantly (p<0.05) higher and serum Zn and urine Creatinine lower in diabetics than non-diabetic subjects. No significant (p>0.05) difference was observed in serum Mg levels of both groups. There were no significant (p>0.05) differences in the serum and urine Zn and Mg levels in diabetics with poor glycemic control (HbA1c > 8.0%) and those with good glycemic control (HbA1c < 8.0%), however, significantly higher urinary Zn and Mg and lower serum Zn levels were observed in diabetic subjects with poor glycemic control when compared with the non diabetic population. Significant positive correlations were observed between serum Zn and serum Mg (p<0.01, r = 0.473), and between urine Zn and urine Mg levels (p<0.01, r = 0.495), while significant negative correlation was observed between serum Mg and urine Mg levels of the diabetic population of the study. Diabetes and poor glycemic control alters the metabolism of Zinc and Magnesium by increasing their urinary excretion and lowering serum Zinc levels. The clinical implications of this are discussed.